Լսողության խանգարումներ ունեցող երեխաների վաղ օգնությունն ընտանիքում - Սարատիկյան, Լիլիթ; Բալաբեկյան, Լիդա (Զանգակ հրատ.)
В статье представлены значение, проблемы, пути ранней помощи детям с нарушеннями слуха в семье и основные направления ранних реабилитационных работ. The article touches upon the importance of early assistance of children having hearing problems in the families, the main problems related to it, as well as the ways and directions of rehabilitation activities of early assistance.
Keywords: Ուսուցման և դասավանդման մեթոդիկա